Late onset thrombosis in two Japanese patients with compound heterozygote protein S deficiency. Issue 6 (June 2015) - Taniguchi, Fumina; Morishita, Eriko; Sekiya, Akiko; Yamaguchi, Daisuke; Nomoto, Haruka; Kobayashi, Erina; Takata, Mao; Kosugi, Ikuko; Takeuchi, Nobuyasu; Asakura, Hidesaku; Ohtake, Shigeki
Highlights: This case report described two patients with compound heterozygote PS deficiency. In two cases, we identified Ala139Val and c.2135delA mutation in PROS1 gene. Both proband developed late-onset thrombosis. Ala139Val mutation might have a mild phenotype. Qualitative deficiency (Ala139Val) may cause development of late-onset thrombosis.